How to diagnose heart failure with preserved ejection fraction: the HFA-PEFF diagnostic algorithm: a consensus recommendation from the Heart Failure Association (HFA) of the European Society of Cardiology (ESC) - Pieske, Burkert; Tschöpe, Carsten; de Boer, Rudolf A; Fraser, Alan G; Anker, Stefan D; Donal, Erwan; Edelmann, Frank; Fu, Michael; Guazzi, Marco; Lam, Carolyn S P; Lancellotti, Patrizio; Melenovsky, Vojtech; et al. (European journal of heart failure, 2020)
Making a firm diagnosis of chronic heart failure with preserved ejection fraction (HFpEF) remains a challenge. We recommend a new stepwise diagnostic process, the 'HFA-PEFF diagnostic algorithm'. Step 1 (P=Pre-test assessment) is typically performed in the ambulatory setting and includes assessment for heart failure symptoms and signs, typical clinical demographics (obesity, hypertension, diabetes mellitus, elderly, atrial fibrillation), and diagnostic laboratory tests, electrocardiogram, and echocardiography. In the absence of overt non-cardiac causes of breathlessness, HFpEF can be suspected if there is a normal left ventricular (LV) ejection fraction, no significant heart valve disease or cardiac ischaemia, and at least one typical risk factor. Elevated natriuretic peptides support, but normal levels do not exclude a diagnosis of HFpEF. The second step (E: Echocardiography and Natriuretic Peptide Score) requires comprehensive echocardiography and is typically performed by a cardiologist. Measures include mitral annular early diastolic velocity (e'), LV filling pressure estimated using E/e', left atrial volume index, LV mass index, LV relative wall thickness, tricuspid regurgitation velocity, LV global longitudinal systolic strain, and serum natriuretic peptide levels. Major (2 points) and Minor (1 point) criteria were defined from these measures. A score ≥5 points implies definite HFpEF; ≤1 point makes HFpEF unlikely. An intermediate score (2-4 points) implies diagnostic uncertainty, in which case Step 3 (F1 : Functional testing) is recommended with echocardiographic or invasive haemodynamic exercise stress tests. Step 4 (F2 : Final aetiology) is recommended to establish a possible specific cause of HFpEF or alternative explanations. Further research is needed for a better classification of HFpEF.
Keywords: Heart Failure; algoritmy; Stroke Volume; Consensus; Humans; lidé; srdeční selhání; senioři; Aged; konsensus; tepový objem; kardiologie; Cardiology; Algorithms